(untitled) (Nordic Journal of African Studies, 2008)
This paper is hinged on the following proposition: that in no other region in Africa are the arguments about the role of the artist in the "public" sphere more intense as is the case in North Africa; that the problematic of what constitutes the "public" sphere in North Africa is circumscribed by the struggle for and the contest over "power", "status" and "authority"; that the attempt by North African writers, particularly Najib Mahfuz (d. 2006), to mirror the socio-political and cultural fissures and contradictions in the public sphere usually lead to conflict, not only over what constitutes the "public sphere" and who governs it, but equally on how the "private" and the sphere "in-between" - in its quintessential slippery and highly charged textures - could be reclaimed for the "public good". In grappling with the foregoing the paper rereads Najib Mahfuzâ€™s AwlÄd HÄratinÄ (Children of our Quarter 1959). In reading for "meaning" and the "meaning of meaning" in the novel the paper pays attention to the socio-political and cultural "codes" provided by Najib Mahfuz even as it searches for possible theoretical insights that the works of Arab-African and Euro-American writers, including Ibn Qayyim, Abdul QÄhir al-JurjÄnÄ«, Edward Said, Michel Foucault and Benhabib, could yield in an excursus which probes into how the trialetic of "power", "status" and "authority" continues to shape the "public", the "private" and the sphere "in-between" of the Egyptian society.